Formulating Ginger Extract, Modified Cassava Flour (Mocaf) and Wheat Flour in Crispy Ginger - Rejeki, Fungki Sri; Wedowati, Endang Retno; Puspitasari, Diana (2477 - 6165, 2025)
This study aims to determine the best composition related to the proportion of wheat flour and mocaf in processing crispy ginger and developing gluten-free food products. The study used factorial experiments with the first factor being proportion of mocaf and wheat flour (P1) consisting of three treatment levels are P1 (mocaf: wheat flour= 50:50), P2 (mocaf: wheat flour= 75:25), and P3 (mocaf: wheat flour= 100:0). The second factor was the concentration of ginger extract (J), consisting of three treatment levels are J1 (ginger extract concentration 20%), J2 (ginger extract concentration 30%), and J3 (ginger extract concentration 40%). The results of the study showed that the proportion of mocaf and wheat flour decreased protein, fat, and water content, but increased carbohydrate and antioxidant content in the crispy ginger. The concentration of ginger extract increased protein, fat, water, and antioxidant content but decreased carbohydrate content in the crispy ginger. Organoleptic testing showed that colour, aroma, taste, and texture were undesirable. The findings of this study indicate that the production of crispy ginger has potential, but improvements are needed for colour, aroma, taste, and texture parameters. The selected treatment alternative was the P2J2 treatment.